Agomelatine : its role in the management of major depressive disorder - Cardinali, Daniel Pedro (2012)
Fil: Cardinali, Daniel P. Pontificia Universidad Católica Argentina. Facultad de Ciencias Médicas. Departamento de Docencia e Investigación; Argentina